Fruquintinib inhibits the migration and invasion of colorectal cancer cells by modulating epithelial-mesenchymal transition via TGF-β/Smad signaling pathway - Qinqin Song; Qinqin Song; Hongjiao Wu; Ye Jin; Junzhi Hou; Jiawei Liu; Xuemei Zhang; Wanning Hu; Wanning Hu; Guogui Sun; Zhi Zhang (Frontiers in Oncology)
BackgroundFruquintinib, a selective vascular endothelial growth factor receptor (VEGFR) inhibitor, has shown considerable efficacy in colorectal cancer (CRC) treatment. Despite its promising therapeutic effects, the precise molecular mechanisms underlying its therapeutic effects remain incompletely understood. In this study, we explored the functional roles and molecular mechanisms of fruquintinib in CRC therapy.Material and methodsHuman CRC cells (HCT-116 and LOVO) were cultured and treated with fruquintinib. Cell counting kit-8 assay kit (CCK-8) and colony formation assays were performed to investigate the effects of fruquintinib on cell proliferation. Wound healing and transwell assays were conducted to explore the role of fruquintinib on migration and invasion. RNA sequencing and bioinformatics analysis was used to investigate the potential mechanism of fruquintinib in the development of CRC. Western blot was used to measure the protein level.ResultsFruquintinib significantly inhibited the proliferation, migration, and invasion of colorectal cancer cells. Bioinformatics analysis indicated that fruquintinib modulated the epithelial-mesenchymal transition (EMT) pathway, and experimental validation confirmed its regulatory effects on core EMT-associated protein biomarkers. Notably, fruquintinib treatment resulted in the upregulation of E-cadherin and the downregulation of N-cadherin, vimentin, and MMP9. Western blot analysis revealed that fruquintinib dose-dependently suppressed SMAD2/3 expression. Notably, treatment with the TGF-β receptor agonist KRFK TFA attenuated fruquintinib’s effect, reversing the upregulation of E-cadherin as well as the downregulatin of N-cadherin and SMAD2/3. Additionally, KRFK TFA partially restored CRC cell migration and invasion in transwell assays, counteracting fruquintinib’s inhibitory impact.ConclusionThese findings indicate that Fruquintinib effectively hampers the migration and invasion of CRC cells by disrupting the EMT process via the TGF-β/Smad signaling pathway. This study sheds light on the mechanisms by which fruquintinib inhibits CRC progression and underscores its potential for further clinical investigation.